As configurações de família em livros didáticos de ciências do 1º ano do ensino fundamental - Silva, Lídia Andrade (2021)
This research is linked to the Post Graduation Program on Education from the Federal University of Uberlândia within the scope of the Education in Science and Mathematics Research Line, and aimed to characterize the family configurations in Science textbooks of the first year of Elementary School, seeking to problematize the crossings within issues of gender and sexual orientation. This objective was segmented into the following specific objectives: problematize the conditions that enabled the family theme to emerge in Science books; and discuss the crossings within the issues of gender and sexuality from the family configurations characterized in the analyzed textbooks. The theoretical foundation came from studies of family, gender and sexuality based on researchers of the area. As methodological analysis we can say it is a qualitative study having the documental research as a tool. The research corpus included four didactic collections of Science from the 1st year of Elementary School. The analysis of the documentary production on the characterization of family configurations in Science textbooks was inspired by the Content Analysis which enabled the building of the categories and subcategories based on the concepts of family and sexuality device and provided the possibility to problematize the different configuration characters featured in the science textbooks examined. The following analysis categories were chosen: I- family models in science textbooks; II- the crossings of gender and sexuality in family configurations present in science textbooks and from these configurations subcategories were created such as: IA- heterosexual family; IB- single parent family; IC- homoparental family; IIA- the reproduction family and the performance of the sexuality device; IIB- family as a place of care and affection; IIC- consanguinity and family ties. The main conclusions of the study indicate that textbooks from the early years of Elementary School reinforce discourses about family, gender and sexuality and they teach standards of normality and accommodation among subjects and that is the reason why we need to build a critical - pedagogical look at the use of these teaching materials and should, based on them, build dialogues with the areas of gender and sexuality in order to think critically about education. The problematizations present in this dissertation text are limited to a given historical and social moment as there is no absolute, finished and ready truth about textbooks, about gender and sexuality and not even about families.